Snapdragon - Leyh, Kat (New York : First Second, 2020)
"Snap's town has a witch. At least, that's the rumor. In reality, Jacks is just a Crocs-wearing, internet-savvy old lady who sells the skeletons of roadkill online. It's creepy, sure, but Snap thinks it's kind of cool, too. Snap needs a favor from this old woman, though, so she begins helping Jacks with her strange work. Snap gets to know her and realizes that Jacks may in fact have real magic--and an unlikely connection to Snap's family's past"--Back cover.
new kids book 2022 fall.
School Library Journal starred, January 2020
Booklist starred, February 2020
Pub Weekly, November 2019
Kirkus Starred, December 2019
Bulletin (Center for Children's Books), February 2020
Keywords: Supernatural -- Fiction; Witches -- Fiction; Magic -- Fiction; Girls -- Fiction; Single-parent families -- Fiction; Marginality, Social -- Fiction; Family secrets -- Fiction; Graphic novels